Legal Accountability for Criminal Actors Without the Right to Sell Narcotics (Study of Decision No. 416/Pid.Sus/2024/PN.Btm) - Sianturi, Patar Mangoloi; Gunarto, Gunarto (UNISSULA Semarang, 2025)
The purpose of this research is to analyze the construction of criminal acts without the right to sell narcotics in the concept of legal certainty, to analyze legal responsibility for perpetrators of criminal acts without the right to sell narcotics (Study of Decision No. 416/Pid.Sus/2024/PN.BTM The approach method used in this study is the normative legal approach method. This method is used considering that the problems to be discussed are related to the construction of criminal acts without the right to sell narcotics in the concept of legal certainty, analyzing legal responsibility for perpetrators of criminal acts without the right to sell narcotics (Decision Study No. 416 / Pid.Sus / 2024 / PN.BTM The results of the study indicate that the crime of selling narcotics without the right in the concept of legal certainty is regulated in Article 114 of Law Number 35 of 2009 concerning Narcotics for class I narcotics. The concept of legal certainty is expressly regulated in the article regarding the provisions and sanctions for criminal liability for a person acting as a narcotics intermediary in the decision number 416 / Pid.Sus / 2024 / PN.BTM in the eyes of the judge, namely the defendant with the initials P by carrying out the sentence imposed by the judge in the form of imprisonment for 9 (nine) years and 6 (six) months and a fine of Rp. 2,125,000,000 (two billion one hundred and twenty-five million rupiah with the provision that if the fine is not paid, it will be replaced with imprisonment for 3 (three) months, and the defendant did not file any legal action at all Based on the research results, it shows that legal certainty in the Narcotics Law is in accordance with legal certainty.